Nothobranchius balamaensis (Cyprinodontiformes: Nothobranchiidae), a new species of annual killifish from northern Mozambique - Bragança, Pedro H. N.; Bellstedt, Dirk U.; van Der Merwe, P. De Wet; Cotterill, Fenton P.d.; Watters, Brian R.; Chakona, Albert (Zootaxa, 2022)
A new seasonal killifish of the genus Nothobranchius is described from the Montepuez River system in northern Mozambique. The new species, Nothobranchius balamaensis Bragança & Chakona, is differentiated from congeners by its characteristic colour pattern and molecular data further support its taxonomic distinctiveness. Phylogenetic results based on two mitochondrial and three nuclear genes confirms N. balamaensis is closely related to N. kirki and N. wattersi; all three belonging to the Coastal-Inland Clade. The new species is most similar in colour pattern to N. kirki sharing the characteristic of a deep red-orange colouration in the basal, proximal, and medial zones of the caudal and anal fins that grades to orange in the distal zone. This is a key feature that distinguishes these two species from all other Nothobranchius. The main distinguishing features between the new species and N. kirki is the presence of a light blue to white band or series of irregular markings in the proximal zone of the anal fin in N. kirki, versus the absence of such a colour pattern element in N. balamaensis, as well as differences in the dorsal fin pattern. When compared to all population groups of N. wattersi, the colour pattern of N. balamaensis is distinctive. Nothobranchius balamaensis is a relatively slender member of the genus, a characteristic that clearly distinguishes it from both N. kirki and N. wattersi. Nothobranchius balamaensis is currently only known from a few specimens from the type locality.